ANALISIS PERENCANAAN LABA DENGAN PENERAPAN TITIK IMPAS PADA PERUMDA AIR WAIR PU’AN KABUPATEN SIKKA - Elisabeth Yessi Da Rato; Yosefina Andia Dekrita; Kristiana Reinildis Aek (ITB AAS INDONESIA, 2024)
The background of this research is the low income of Wair Pu'an Regional Water Supply, Sikka Regency for five years, starting from 2018 to 2022. This study aimed to determine profit planning with the BEP approach at Wair Pu'an Regional Water Supply, Sikka Regency. The data sources in this study were primary data in the form of direct interviews with Wair Pu'an Regional Water Supply, Sikka Regency, secondary data in the form of Balance Sheet and Income Statement and employee salary data at Wair Pu'an Regional Water Supply, Sikka Regency. The data was analyzed using BEP analysis. The results of the BEP calculation showed that to break even the company had to make a profit in 2018 of IDR 28,527,998.221, in 2019 of IDR 39,285,460,544.37, in 2020 of IDR 42,097,758.69, in 2021 of IDR 45,177,242,941.55, in 2022 of IDR 41,120,058,831.337. This was inversely proportional to what was experienced by Wair Pu'an Regional Water Supply, Sikka Regency, which always got revenue below the BEP. From the results of the analysis it was known that Wair Pu'an Regional Water Supply, Sikka Regency had not been able to reach the BEP, which directly indicated that the company was experiencing a loss or deficit.